Evaluation of immunological markers of ovine vaginal irritation: Implications for preclinical assessment of non-vaccine HIV preventive agents - Milligan, Gregg N. (J Reprod Immunol, 2017)
The presence of genital inflammatory responses and a compromised vaginal epithelial barrier have been linked to an increased risk of HIV acquisition. It is important to assure that application of candidate microbicides designed to limit HIV transmission will not cause these adverse events. We previously developed high resolution in vivo imaging methodologies in sheep to assess epithelial integrity following vaginal application of a model microbicide, however characterization of genital inflammation in sheep has not been previously possible. In this study, we significantly advanced the sheep model by developing approaches to detect and quantify inflammatory responses resulting from application of a nonoxynol-9-containing gel known to elicit vaginal irritation. Vaginal application of this model microbicide resulted in foci of disrupted epithelium detectable by confocal endomicroscopy. Leukocytes also infiltrated the treated mucosa and the number and composition of leukocytes obtained by cervicovaginal lavage (CVL) were determined by differential staining and flow cytometry. By 18 h post-treatment, a population comprised predominantly of granulocytes and monocytes infiltrated the vagina and persisted through 44 h post-treatment. The concentration of proinflammatory cytokines and chemokines in CVL was determined by quantitative ELISA. Concentrations of IL-8 and IL-1β were consistently significantly increased after microbicide application suggesting these cytokines are useful biomarkers for epithelial injury in the sheep model. Together, the results of these immunological assessments mirror those obtained in previous animal models and human trials with the same compound and greatly extend the utility of the sheep vaginal model in assessing the vaginal barrier and immune microenvironment.